Implementation of Explicit Instruction Strategy in Muhadatsah Material for ADHD Students in Inclusive Classrooms - Laili Mas Ulliyah Hasan; Muhammad Tareh Aziz; Muhammad Rido’i (Universitas Islam Tribakti Lirboyo, Kediri, 2026)
Teaching muhadatsah (Arabic conversation) in inclusive classrooms presents challenges, particularly for students with Attention Deficit Hyperactivity Disorder (ADHD) who experience difficulties in attention regulation, focus, and verbal expression. Previous studies have discussed ADHD in general language learning contexts; however, research focusing on muhadatsah instruction using structured strategies in inclusive Islamic secondary schools remains limited. This study aims to examine the implementation of the Explicit Instruction strategy in muhadatsah learning to enhance engagement, speaking confidence, and communication independence among ADHD students. This research employed a qualitative approach with a case study design conducted at MTs Wachid Hasyim Surabaya. The participants consisted of five eighth-grade students diagnosed with ADHD, one inclusive education teacher, and Arabic language subject teachers as key informants. Data were collected through classroom observations, semi-structured interviews, and documentation of learning activities, and analyzed using thematic analysis involving data reduction, categorization, and interpretation. The findings indicate that Explicit Instruction, supported by visual media and paired practice, facilitated students’ understanding of sentence structures, increased verbal participation, and encouraged greater independence in responding during muhadatsah activities. Indicators of effectiveness were observed in improved attention during learning, increased speaking courage, more frequent student-initiated responses, and reduced dependence on teacher guidance. This study highlights the uniqueness of applying Explicit Instruction in muhadatsah learning as an adaptive and effective approach for addressing the specific needs of ADHD students in inclusive Islamic school settings.